How Environmental, Social, and Governance Reporting Drives Innovation Capability and Firm Value in Indonesia - Rizka Hadya; Syukri Lukman; Masyhuri Hamidi; Rahmat Febrianto; Irdha Yusra (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2026)
This research extends the resource-based explanation of firm value by analyzing innovation capability as both a key driver of Tobin's Q and as an effect of environmental, social, and governance (ESG) disclosures. Using panel data from 82 listed firms on the Indonesia Stock Exchange over a decade (820 observations), we employed fixed-effects regression based on Chow and Hausman tests. The analysis proceeded in two stages: first, examining how the three ESG disclosure pillars influence innovation capability, and second, how innovation capability impacts firm value, controlling for size, age, leverage, and board size. The findings reveal that only social disclosure significantly enhances innovation capability, while environmental and governance disclosures do not show notable effects. Moreover, increased innovation capability leads to a substantial and significant improvement in firm value. While firm size and board size positively affect value, firm age has a negative impact. The evidence points to an asymmetry: whereas social disclosure supports capability-building, innovation capability itself is a strong channel through which market value is realized, and this mechanism in Indonesia relies mainly on the social aspect of ESG, rather than environmental or governance disclosure volume. This work refines the resource-based perspective for developing economies and offers targeted insights for business leaders and policymakers about which ESG areas most effectively foster strategic advantage.